2020
DOI: 10.3389/fmicb.2020.00785
|View full text |Cite
|
Sign up to set email alerts
|

Complete Mitochondrial Genome of the Fungal Biocontrol Agent Trichoderma atroviride: Genomic Features, Comparative Analysis and Insight Into the Mitochondrial Evolution in Trichoderma

Abstract: The improvement of biopesticides for use in the agriculture industry requires an understanding of the biological-and ecological principles underlying their behavior in natural environments. The nuclear genomes of members of the genus Trichoderma, which are representative fungal biocontrol agents, have been actively studied in relation to the unique characteristics of these species as effective producers of CAZymes/secondary metabolites and biopesticides, but their mitochondrial genomes have received much less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 73 publications
6
19
0
Order By: Relevance
“…Thus far, most studies of fungal mitogenomes have focused on the (1) sequencing and characterization of individuals and (2) the elucidation of their phylogenetic positions within its relatives to support the potentials for one of the significant molecular markers identifying fungal species. Until recently, few studies have reported on comparative analyses of mitogenomes, ranging from a taxa level for specific fungal groups, under evolutionary viewpoints [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, most studies of fungal mitogenomes have focused on the (1) sequencing and characterization of individuals and (2) the elucidation of their phylogenetic positions within its relatives to support the potentials for one of the significant molecular markers identifying fungal species. Until recently, few studies have reported on comparative analyses of mitogenomes, ranging from a taxa level for specific fungal groups, under evolutionary viewpoints [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The largest intergenic region was between nad5 and cob genes. Meanwhile, in the T. reesei QM 9414 mitogenome, the species with the largest mitogenome in the genus, the intergenic regions accounted for a total of 7,405 bp (17.58% of total mitogenome), similar to the latter (Kwak 2020). So in this genus, it could be suggested that the intergenic regions were not an important force modeling mt genomic size variation.…”
Section: Intronic and Intergenic Regionsmentioning
confidence: 94%
“…Mitochondria (mt) use electron transport coupled with oxidative phosphorylation to generate ATP and these organelles also participate in several other cellular important functions [1]. Mitochondrial DNA or mitochondrial genome, also known as mitogenome, is made up of genes that encodes a small number of proteins whose mRNAs are translated by a distinctive mitochondrial protein-synthesizing system Burger et al 2003;Kwak 2020). Evolutionarily mitogenome exhibit remarkable variation in conformation, size, actual gene content, arrangement and expression (Gray et al 1999;Li et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations